The impact of COVID-19 imposed lockdown in India in 2020 - Sahanaa, Chandar; Murugan, Yuvaraja (International Journal Of Community Medicine And Public Health, 2021)
The World Health Organization declared COVID-19 pandemic as Public Health Emergency of International Concern on January 30, 2019. Lockdown was introduced as a preventive strategy to reduce the community transmission of the SARS CoV-2. This paper throws light into some unseen circumstances and challenges faced during the COVID-19 pandemic imposed lockdown. Socio-economic and healthcare crises, plight of migrants, mental health of women during the lockdown, stressful online classes for students and teachers, etc are few challenges faced during the period. However few noteworthy incidents during lockdown includes use of virtual reality in the field of telemedicine, couples on infertility treatment managed to concieve naturally, other survivors in the ecosysytem like birds and animals have enjoyed the environment. To conclude the pandemic imposed lockdown has not only helped in prevention and control of infectious diseases but also reminded us to address the new lifestyle changes and rising burden of mental health.